2012
DOI: 10.1097/bot.0b013e3182460837
|View full text |Cite
|
Sign up to set email alerts
|

Operative Versus Nonoperative Treatment of Unstable Lateral Malleolar Fractures

Abstract: Patients managed operatively had equivalent functional outcomes compared with nonoperative treatment; however, the risk of displacement and problems with union was substantially lower in patients managed with surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
119
3
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(126 citation statements)
references
References 22 publications
(25 reference statements)
1
119
3
3
Order By: Relevance
“…78 This is, however, just one domain of health-related quality of life. Utility at each time point was not reported and thus it is not possible to explain the nature of the (imprecise) QALY difference in the Slobogean et al analysis.…”
Section: Health Economic Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…78 This is, however, just one domain of health-related quality of life. Utility at each time point was not reported and thus it is not possible to explain the nature of the (imprecise) QALY difference in the Slobogean et al analysis.…”
Section: Health Economic Evaluationmentioning
confidence: 99%
“…78 The study included 81 participants who had an isolated, undisplaced, unstable, type B fracture of the distal fibula. Participants were younger than those in the AIM trial, aged, on average, 41 years.…”
mentioning
confidence: 99%
“…19 Sanders et al in 2012 conducted a randomized multicenter trial to compare clinical and functional outcomes after operative and non-operative treatment of undisplaced, unstable, isolated fibula fractures and concluded that patients managed operatively had equivalent functional outcomes compared with non-operative treatment; however, the risk of displacement and problems with union was substantially lower in patients managed with surgery. 20 Berkes et al in 2013 examined the impact of articular surface congruity on the functional outcomes of operative treatment of supination external rotation IV ankle fractures. Post-operative CT scans were used to assess ankle joint congruity.…”
Section: Inferencementioning
confidence: 99%
“…Conservative care of non-displaced fractures usually results in satisfactory outcomes for patients, and has lower risk profiles than operative treatment [6]. However, non-unions do occur and several ways have been documented on how to treat them [3].…”
Section: Discussionmentioning
confidence: 99%
“…When a fibula is fractured, 75-85% of the time it occurs concomitantly with a tibia fracture, often due to a rotational injury [2][3][4][5]. Stability of the fracture is assessed and when it is stable and non-displaced, conservative treatment is recommended, with satisfactory results [2,6]. This includes 6-8 weeks of protected or non-weight bearing in an immobilizing boot or below knee cast.…”
Section: Introductionmentioning
confidence: 99%